ETR 300 : X-Treme Games Shop / Muhamad Sani Saari ... [et al.] - Saari, Muhamad Sani; Johari Ariffin, Syed Fateh; Sulaiman, Mohd Fauzi; Hussin, Nurul Masha; Ismail, Izam Syah (2002)
The idea behind establishing X-Treme Games Shop is to provide items and equipment relates with extreme games. This transaction involved directly to the customer. To be successful entrepreneur, one must be a risk taker. We dare to take the risk because we can see the advantage in doing this kind of business even though these kind of game come from the western and seem to be new here in Malaysia. X-Treme games usually played by youths and teenagers which required certain kind of skills, experiences, styles, practices, disciplines and the most important is patient of the players. X-Treme games can be divided into two main categories. The first category can be played in the designated places, for example skate board, roller blade, BMX and wall climbing. Another category can be played in the nature places, for example mountain bike, dirt bike and kayaking. From our survey we found that this kind of business is rarely found in Malaysia. This is because not many of the entrepreneurs dare to take the risk and challenge to run this business. Another reason is lack of suppliers in this field. However we dare to take the risk because for many reasons.